Critical Financial Education in Teacher Education: an approach that problematizes different social contexts - Sousa, Mario Rogério Vasconcellos de; Matos, Diego (Educação Matemática Debate, 2025)
This study investigates the perceptions of Mathematics undergraduates about Financial Education, when confronted with a critical approach that contrasts different social contexts. The research was carried out with five undergraduates from a federal university in Rio de Janeiro, in two stages of data production: (1) a task on the concept of interest and decision-making; (2) an online conversation circle, with semi-structured questions and a fictitious classroom episode, confronting different social contexts that can manifest themselves at school. As a result of the research, we identified three perceptions of Financial Education in the context of its formative role: (a) personal financial management and capital accumulation; (b) critical social formation; (c) Mathematics as (in)certainty: regulation or social questioning?